TINGKAT PENGGUNAAN BAHAN KIMIA BERBAHAYA PADA PENGOLAHAN IKAN ASIN: KASUS DI MUARA ANGKE DAN CILINCING, JAKARTA - Ernik Yuliana; Deddy Ahmad Suhardi; Adhi Susilo (Jurnal Pengolahan Hasil Perikanan Indonesia, 2011)
Salted  sh is still prefered by community of Indonesia. Salted  sh processing by traditional method depent on the intensity of sunlight. To reduce depence, some processors used chemicals as a preservative. The purpose of the study is identi ed the level of use of hazardous chemicals in salted the processing of salted  sh. The research’s design was explanatory research design. The population were all of the salted  sh processors in Muara Angke andCilincing, North Jakarta. Respondent choosen randomly to get 73 salted  sh processors, 55 persons of them were located at Muara Angke and another 18 were from Cilincing. Data collected consist of primary data, used survey methods. Then data was analysed with descriptif-analysis and Rank Spearman correlation. The results indicated that the hazardous chemicals (formalin and bleach) were still used by the processor. Level of usage hazardous chemicals is signi cantly associated with perception processors of consumer knowledge. Education of consumers about the hazardous chemicals needs to be improved so that consumers did not want to buy salted  sh products with chemicals, thereby to suppress the use of chemicals in the processing of salted  sh. Government oversight of the use of hazardous chemicals was still relatively low, so that should be improved to encourage processors to be willing to process naturally salted  sh and leave the chemicals.Keywords: chemicals, government oversight, salted  sh, salted  sh processor